Introducing the otam: Exploring users' perceptions of their on-going interaction with adopted technologies - Knight, Shirlee-ann; Burn, J. (2011)
A common criticism directed at Davis’ (1986; 1989) Technology Acceptance Model relates to its failure to adequately frame the “experienced” user’s ongoing adoption and exploitation of information technologies. Given the pervasive nature of technology into individual users’ ongoing, everyday communication and information interactions, along with the “new adopter” becoming an increasingly rare entity, the TAM is in danger of becoming a somewhat obsolete framework for investigating user-technology interaction. Presented is a critical analysis of the development and current state of the TAM, followed by a proposed addition to the existing Perceived Usefulness (PU) and Perceived Ease of Use (PEoU) TAM constructs. The paper contends that the inclusion of a Perception of Interaction (PoI) construct allows researchers to develop an investigative framework which facilitates an exploration of users’ ongoing perceptions of the predictability of their technology interaction processes.